Penguatan Literasi Saintifik-Religius Siswa SD Alam Bireun melalui Pembelajaran Kontekstual Jam Matahari - Hasna Tuddar Putri; Laiyina Ukhti; Ravik Walhidayah; Raisa Salsabiila (Universitas Negeri Gorontalo, 2026)
Students at Sekolah Alam Bireuen (SABIR) in Aceh continue to experience difficulties in relating observable astronomical phenomena to the determination of prayer times, despite the school’s nature-based learning approach. This situation indicates the need for instructional interventions that integrate scientific concepts with religious practices. This community service program aimed to strengthen students’ scientific–religious literacy through the use of sundials as basic observational instruments. Using the Participatory Action Research (PAR) method, 25 third- and fourth-grade students participated in classroom sessions introducing Islamic astronomy and outdoor activities involving the construction and observation of simple sundials. During the outdoor practice, students positioned gnomons, marked shadow movements, and observed the shortest shadow as the Sun passed its culmination point. The observations describe students’ emerging understanding of the relationship between the Sun’s position and the onset of prayer times, along with their developing skills in using simple astronomical tools. This program provides an account of how empirical engagement with natural indicators can support integrated learning that connects scientific reasoning with religious values.